Intravascular schwannoma as an extremely unusual cause of vein obstruction: a case report - Luis Miguel Chinchilla-Tábora; Beatriz Segovia Blázquez; José María Sayagués; Marta Rodríguez González; Joaquín González-Rivero; José Antonio Muñoz León; Andrea Beatriz Jiménez Pérez; Idalia González Morais; Diego Bueno-Sacristán; María Dolores Ludeña (Korean Society of Pathologists & the Korean Society for Cytopathology, 2024)
The blood vessel lumen is an extremely rare location for a benign peripheral nerve sheath tumor like schwannoma. Less than 10 cases have been previously reported. In this report, we present a case of a 68-year-old woman who had a soft tissue nodule at the posterior calf of her left leg during a physical examination. Pathological examination was performed after complete surgical excision. The patient underwent follow-up for 12 months after surgery without evidence of recurrence or any other complication. This is the first case of intravascular schwannoma reported as a cause of vein obstruction. Microscopically, the tumor was composed of Schwann spindle cells that were immunoreactive for S100 protein and SOX10. This tumor was surrounded by a well-defined vascular smooth muscle wall. Prospective series are required to improve the knowledge on the underlying mechanisms of intravascular schwannoma development.